Building Legal Awareness and Democracy: Revitalizing the Role of Citizenship Education for Students of SMAN 7 Kediri City - Bramantyo, Rizki Yudha; Pujiono, Bambang; Wahyuni, Niniek (Transparansi Hukum, 2021)
ABSTRACT Recently, a lot of students have participated in demonstrating against government policies. Even though, they do not know the detailed contents of the government policies they are about. In fact, in practicing democracy, it is not uncommon for them to violate the law by committing acts of anarchy, destroying public facilities, and other acts of fandalism. The purpose of this research is to describe qualitatively about the role of Citizenship Education in increasing legal awareness and awareness of democracy. The method used is descriptive qualitative. The research was conducted At the SMAN 7 Kediri Kediri City. The research subjects were school principals, students, Civics teachers and Guidance and Counseling Teachers. Data were collected using participatory observation methods and in-depth interviews. Data relating to documents owned by the school were collected using the library documentation method. The data that has been collected is analyzed using methods of: 1) data collection, 2) data classification, 3) data filtering, and 4) drawing conclusions. To improve the accuracy and consistency of the data, triangulation methods in the form of snowballing were used, prolonged stay at the research location, and made temporary conclusions until data saturation was reached. The results showed that, Citizenship Education was able to increase legal awareness and was able to increase democratic awareness among students of SMAN 7 Kota Kediri. Keywords : Education, citizenship, law, democracy, students